Casa virtual em BIM: uma proposta didática para o uso de modelos virtuais no ensino de projetos em ateliê de arquitetura - Lima, Alcilânia da Cunha (2025)
This dissertation investigates the use of virtual models in Building Information Modeling (BIM) as a teaching tool in teaching architectural projects in Architecture Studio. With the increasing digitalization of design processes, it is essential to explore methodologies that integrate innovative technologies into teaching, providing students with a more interactive and efficient learning experience. The study proposes the "Virtual House in BIM", an approach that uses three dimensional parametric models to support the development and understanding of architectural concepts, improving communication and project analysis, through learning paths and analytical rubrics. The research adopts a qualitative methodology, with case studies and classroom experimentation, analyzing the impacts of this strategy on student training. The results indicate that the use of virtual models facilitates spatial visualization, interdisciplinary coordination and the assimilation of constructive and technological aspects of the project. Furthermore, the approach contributes to the development of critical thinking and collaborative work among students. It is concluded that the incorporation of BIM in architecture teaching not only modernizes the pedagogical process, but also prepares future architects for the challenges of the professional market.